A historical geography of housing crisis in Australia. Issue 1 (2nd January 2018) - Dufty-Jones, Rae
ABSTRACT: Much of the current debate on Australian housing affordability suggests that it is a new 'crisis'. Yet Australia's housing history is littered with a series of housing crises, and since the early days of white settlement in Australia the availability of housing has been an ongoing governmental concern. The focus of this paper is on the 1940s housing crisis that contributed to housing becoming one of the cornerstones of the federal government's post-war reconstruction agenda. This paper adopts a governmentality theory perspective to explore how Australia's housing problems and solutions were constructed during this period, through an in-depth textual analysis of key documents produced at the time. The wider project of post-war reconstruction was understood to have important spatial dimensions. As a consequence, both the problematisation of housing and the design of housing policy as a solution to these challenges were distinctly spatial. While the present debate echoes many of the longer-run discourses characterising housing crises, the current axiom that markets are best placed to mediate housing affordability overlooks key lessons from the past: that affordable housing necessarily entails governmental interventions, and geographically imagined problematisations and solutions.